The Intention of Origin Influence Image Country to Buy Smartphone in Indonesia: Case Study on Samsung Brand - Hendro Hendro; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2020)
The purpose of this study to determine effect of origin image country and purchase intention with mediation of brand equity and brand preference. Here, we collect the data from 106 respondents who use smartphone. In this study, the data observation was analyzed using Structural Equation Model (SEM). The results showed that country of origin image had negative effect on brand equity, brand equity had positive effect on the brand preference, and brand preference had an effect on the purchase intention. Please give the calculation comparation between brand equity, brand preference in purchase intention.